NEPAD and Development in Africa: An Analysis - Yusuf, Mohammed Sanni; Salihu, Muhammed Anyimode; Oyigebe, Peter Luke (Kashere Journal of Politics and International Relations, 2025)
This paper examines the New Partnership for Africa’s Development (NEPAD), a significant initiative aimed at transforming Africa’s socio-economic landscape since its launch in 2001. NEPAD was conceived to reposition Africa in global development discourse by addressing key issues such as poverty, governance, infrastructure deficits, and economic integration. This study explores the historical evolution of NEPAD, its objectives, and the strategies employed to achieve sustainable development across the continent. It evaluates NEPAD's achievements, including the promotion of intra-African trade through the African Continental Free Trade Area (AfCFTA), the establishment of the African Peer Review Mechanism (APRM) for governance, and the Comprehensive Africa Agriculture Development Programme (CAADP) for agricultural advancement. However, the paper also highlights significant challenges faced by NEPAD, including dependency on external funding, limited enforcement of governance reforms, infrastructural inefficiencies, and conflicts overshadowing its development agenda. Through a comprehensive analysis, this study underscores the necessity for continuous adaptation and the implementation of practical recommendations aimed at enhancing NEPAD’s effectiveness. By strengthening domestic resource mobilization, enhancing governance mechanisms, prioritizing conflict resolution, facilitating regional cooperation, and investing in capacity building, NEPAD can significantly improve its impact on Africa's development trajectory. Ultimately, this paper contributes to the discourse on regional development strategies in Africa, providing insights into the potential for NEPAD to foster a more integrated, resilient, and prosperous continent.